2020
DOI: 10.1093/eurpub/ckaa165.1201
|View full text |Cite
|
Sign up to set email alerts
|

The health and economic burden of antimicrobial resistance

Abstract: Antimicrobial resistance (AMR) has profound consequences for the treatment of infections. By limiting treatment options, it often makes it necessary to resort to antibiotics with a broader spectrum of action some of which are potentially less effective or safe than narrow-spectrum antibiotics. This limitation in our ability to treat infections effectively has an impact on health care budgets but also broader and potentially disastrous consequences on a variety of economic sectors. This presentation provides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 299 publications
1
4
0
Order By: Relevance
“…This finding is also supported by the study of March-Lopez et al [ 68 ] who reported a significant reduction in the total spending on antibiotics due to reductions in total spending on broad-spectrum antibiotics, and by Walker and colleagues [ 50 ] who stated that the reduction in the cost per claim of antibiotics was mainly triggered by the increasing utilization of generic first-line antibiotics. This is in line with previous literature reporting that the use of broad-spectrum antibiotics, which are commonly more expensive, and alteration in clinicians’ prescription practices, namely the prescription of second-line antibiotics, are considered some of the main drivers behind extra costs in healthcare [ 77 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is also supported by the study of March-Lopez et al [ 68 ] who reported a significant reduction in the total spending on antibiotics due to reductions in total spending on broad-spectrum antibiotics, and by Walker and colleagues [ 50 ] who stated that the reduction in the cost per claim of antibiotics was mainly triggered by the increasing utilization of generic first-line antibiotics. This is in line with previous literature reporting that the use of broad-spectrum antibiotics, which are commonly more expensive, and alteration in clinicians’ prescription practices, namely the prescription of second-line antibiotics, are considered some of the main drivers behind extra costs in healthcare [ 77 ].…”
Section: Discussionsupporting
confidence: 89%
“…In addition to monetary effects, directly related to antibiotics and their associated costs, inappropriate antibiotic prescriptions and dispensing also have negative effects on productivity [ 77 , 78 ]. Productivity losses are related to the amount of work time lost, due to lack and/or non-productivity as a result of reduced concentration, as well as the expected number of additional hours needed to conclude the regular amount of work [ 53 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use, misuse, and overuse of antimicrobials is recognized by the World Health Organization as one of the main public health threats of the 21st century, leading to the accelerated emergence of antimicrobial resistance (AMR) and consequent health and economic burdens [1,2]. Bacteria develop resistance to antimicrobials through a natural process of evolution, classified as intrinsic; acquired via selective pressure associated with the use of a particular antimicrobial, or via horizontal transfer of antimicrobial resistance genes between bacteria [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…AMR occurs when microorganisms stop responding to antimicrobials to which they were previously sensitive to [18] . AMR has fatal consequences as reported by many scholars [17][18][19][20][21][22][23][24] , hence, the need to address it using various strategies [25][26][27][28][29][30][31][32][33][34][35][36] , including the use of traditional medicine1 [7,37] . The emergency of AMR demands a need to promote drug discovery and the development of newer antimicrobials and alternative therapies [2,[38][39][40][41][42][43][44][45] .…”
Section: Introductionmentioning
confidence: 99%